2018
DOI: 10.1111/aab.12460
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Manihot esculenta Crantz germplasm based on single‐nucleotide polymorphism markers

Abstract: Cassava (Manihot esculenta Crantz) is a species whose natural diversity has great food, industrial and energy potential. This study aimed to evaluate the genetic diversity, and population structure of 1,580 accessions belonging to the international germplasm conserved in Brazil using 20,601 single‐nucleotide polymorphism markers. The average values of polymorphic information content (PIC), inbreeding (f), observed heterozygosity (Ho) and expected heterozygosity (He) were 0.24, 0.21, 0.23 and 0.30, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 55 publications
0
17
4
Order By: Relevance
“…SSRs and microsatellite are multi-allelic and are more polymorphic than SNP markers, which are usually bi-allelic. The genetic diversity detected here for enset is higher than what has been reported for some other vegetatively propagated plants such as Cassava (de Albuquerque et al , 2018; Kamanda et al , 2020), and out-crossing plants such as sunflower (Mandel et al, 2011) but lower what has been reported for Japonica rice (Becerra et al, 2017).…”
Section: Discussioncontrasting
confidence: 84%
“…SSRs and microsatellite are multi-allelic and are more polymorphic than SNP markers, which are usually bi-allelic. The genetic diversity detected here for enset is higher than what has been reported for some other vegetatively propagated plants such as Cassava (de Albuquerque et al , 2018; Kamanda et al , 2020), and out-crossing plants such as sunflower (Mandel et al, 2011) but lower what has been reported for Japonica rice (Becerra et al, 2017).…”
Section: Discussioncontrasting
confidence: 84%
“…To better characterize individuals in our population, we mined common loci between our GBS dataset and 62 WGS HapMap individuals from Brazil, creating the 1,536 accession GUH dataset. The observed DAPC structure patterns of 10 groups, corresponding to the stepping stone model as described by Jombart et al (2010), which was fewer than previously reported by (de Oliveira et al 2014; H. Y. G. de Albuquerque et al 2018). From these previous studies in Brazil, some of the genetic groups reportedly had less than ten accessions in them, indicating that they share similar genomic regions.…”
Section: Population Genetic and Geospatial Structurecontrasting
confidence: 64%
“…LD in cross-pollinated species decays more rapidly than among self-pollinated species as a result of more effective recombination that occurs in the former (Zhu et al 2015). The extent of whole genome LD in this study (∼107 kb; r 2 < 0.1) was higher than previously estimated in Brazilian cassava (∼20 kb; r 2 < 0.2) (H. Y. G. de Albuquerque et al 2018), East-West African (∼50 kb; r 2 < 0.2) datasets (Wolfe et al 2016) and for HapMap (3 kb; r 2 = 0.1) (Ramu et al 2017) but lower compared to West African (∼2 Mb; r 2 < 0.1) (Rabbi et al 2017). Among other outcrossing species, LD observed in this study was higher than LD observed for global panel in maize (∼10 kb; r 2 < 0.1) (Yan et al 2009), sweet potato (0.6 kb; r 2 < 0.1, 1.2 kb; r 2 < 0.2) (Wadl et al 2018), yam (100 bp; r 2 < 0.1) (Akakpo et al 2017) and potato (∼275 bp; r 2 < 0.1) (Stich et al 2013).…”
Section: Linkage Disequilibrium and Introgression In Brazilian Germplasmcontrasting
confidence: 62%
See 1 more Smart Citation
“…The characterization of this unique set of 1536 accessions yielded DAPC structure patterns of 10 genetic groups, corresponding to the BIC profile obtained from a stepping stone model as described by Jombart et al (2010). Previous studies from Embrapa reported more genetic groups (> 20) with some of the groups having less than ten accessions (Oliveira et al 2014;Albuquerque et al 2018). The lower probability of individual group assignments (PAI) from DAPC can be related to highly admixed individuals sharing haplotypes segments from multiple clusters identified (Albuquerque et al 2018).…”
Section: Population Genetic and Geospatial Structurementioning
confidence: 99%